Use of UV Treated Milk Powder to Increase Vaccine Efficacy in the Elderly - Schaefer, Sara; Hettinga, Kasper Arthur; Cullor, James; German, J. Bruce; Henrick, Bethany M. (Frontiers in Immunology, 2018)
Aging populations experience a decline in adaptive immune system function also known as immunosenesence. Protein nutrition has been shown to stimulate and strengthen the immune system, and such approaches are needed for this growing segment of the population. A controlled, randomized, double blind pilot study was conducted to compare two different protein sources (soy and dairy) as nutritional supplementation to enhance vaccine response. Our objective was to examine the immune stimulating effects of dairy protein subjected to ultraviolet radiation (UV-C) radiation treatment process instead of pasteurization. Participants were 21 healthy individuals over 60 years of age who consumed 6 g of the dairy protein or a comparison, soy isoflavone protein, twice a day for eight weeks. DTaP vaccine administered at week 4. Non-parametric t-tests revealed a significant increase in Tetanus antibodies in the dairy group compared to the soy group at week 8. These findings suggest additional benefits of UV-C treated unheated dairy protein as a solution to counteract immunosenescence, but warrant further study in elderly and other populations that might benefit from immune system stimulation.